2022
DOI: 10.1039/d2me00049k
|View full text |Cite
|
Sign up to set email alerts
|

Substituent effects on the mechanochemical response of zinc dialkyldithiophosphate

Abstract: Mechanochemistry is known to play a key role in the function of some lubricant additives, such as the tribofilm growth of zinc dialkyldithiophosphate (ZDDP). This raises the intriguing possibility of...

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 86 publications
3
12
0
Order By: Relevance
“…Δ V * is sometimes interpreted as volume change that occurs when the transition state is formed from the reactants. 96 In our simulations, as well as previous experiments of ZDDP tribofilm growth, 8,10,54 Δ V * is positive, indicating that the volume of the transition state is larger than the reactants, confirming that the rate-determining step involves bond breaking. 91 We use shear stress, τ , in eqn (1) rather than normal stress, σ .…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…Δ V * is sometimes interpreted as volume change that occurs when the transition state is formed from the reactants. 96 In our simulations, as well as previous experiments of ZDDP tribofilm growth, 8,10,54 Δ V * is positive, indicating that the volume of the transition state is larger than the reactants, confirming that the rate-determining step involves bond breaking. 91 We use shear stress, τ , in eqn (1) rather than normal stress, σ .…”
Section: Resultssupporting
confidence: 86%
“…Previous experimental studies of mechanochemical tribofilm growth have treated the activation volume as a temperature-independent reaction constant; however, these studies considered a much smaller temperature range than the present study. 8–10,54,91 In our recent NEMD study of trialkyl phophate mechanochemical decomposition, we also observed that the activation volume increased with increasing temperature. 46 This was partially explained through a reduction in the elastic modulus of the α-Fe(110) slabs.…”
Section: Resultsmentioning
confidence: 66%
See 1 more Smart Citation
“…It has recently been found that the activation energy and pre-exponential factors for the rate of mechanochemical decomposition of a well-known lubricant additive, zinc dialkyl dithiophosphate (ZPPD), are in uenced by changing the nature of the function groups that surround the core of the additive [27]. In particular, it has been found that the activation energy for the reaction is accompanied by a corresponding change in the pre-exponential factor, , such that the activation energy varies linearly with .…”
Section: Compensation Effects In Stress-modi Ed Processesmentioning
confidence: 99%
“…This concept is widely used to explain i.e. tribofilm formation and atomic scale wear. On the other hand, in boundary lubrication, the stress activation volume is interpreted as the volume of boundary layer molecules that are moved at the interface during the thermally activated shear process. ,, In the remainder of the paper, the stress activation volume is always referred to in the latter meaning. According to eq , the effective energy barrier for discrete processes underlying relative motion of the boundary layer decreases with the product of the stress activation volume and the applied shear stress. ,, For single-asperity contacts, the dependence of the shear stress on sliding velocity can be accurately captured by the Eyring model. ,,,, However, for larger multi-contact interfaces, it remains challenging to connect the theoretical description of boundary lubrication to experimental observations due to limitations in our ability to measure the area of real contact and, thus, the shear stress. , Moreover, there is no direct method available to locally probe the mobility of boundary layers and connect the activation volume to the free volume of the lubricant.…”
Section: Introductionmentioning
confidence: 99%